Advances of SBAS authentication technologies - Ying Chen (Satellite Navigation, 2021)
Abstract Satellite Based Augmentation System (SBAS) provides the corrections and integrity information to users, but as its signal format is opened to the public and Global Navigation Satellite System (GNSS) spoofing technology becomes more realistic, more feasible and cheaper. It's foreseeable that there will be risks of spoofing threats against SBAS in the future. SBAS signal authentication technology provides a system-level solution to spoofing threats by adding special markers to SBAS signals so that receivers can verify whether the SBAS signals are from the on-orbit Geostationary Earth Orbit (GEO) satellites or whether the signal information has been forged and tampered with. First, this article introduces the existing anti-spoofing methods that can be applied to SBAS, especially the Elliptic Curve Digital Signature Algorithm (ECDSA) and Timed Efficient Stream Loss-Tolerant Authentication (TESLA) protocols. Then it discusses four possible solutions in a combination with the existing SBAS Interface Control Document (ICD). Two main Key Performance Indicators (KPIs), Time Between Authentication (TBA) and Authentication Latency (AL), obtained in the four main scenarios are compared. By analyzing the EGNOS Authentication Security Testbed (EAST) test simulation results of European Geostationary Navigation Overlay Service (EGNOS) in Europe, the impact of SBAS after joining the authentication service is obtained.